Automatic cat feeder / Nur Fatihah Mohd Zainuddin and Norjasween Abdul Malik - Mohd Zainuddin, Nur Fatihah; Abdul Malik, Norjasween (School of Mechanical Engineering, 2023)
People enjoy providing food and water to cats, but they often leave it on the floor or on the road, resulting in cats being exposed to various infections due to food and water contamination. The objectives of this study are to design, analyze, and fabricate an automatic cat feeder with multiple functions. This product is constructed using aluminium composite panel (ACP) and acrylic board. The automatic cat feeder comprises three parts, which are the food part, wire part, and drink part. The total size of the feeder is 600mm x 800mm x 200mm. The product incorporates a timer, motor, and pump. Busy cat owners can use this automatic cat feeder to save time. The timer allows for scheduling, while the pump is used to move fluids. Results from product testing indicate that the maximum dry food mass the product can hold is between 0.1kg and 0.3kg. All the electrical components function properly. In conclusion, this project has successfully achieved all its objectives. The product provides cat lovers and others with the opportunity to provide food and drinks to cats in a sterile environment